ANALYSIS OF DIFFERENTIAL ITEM FUNCTION (DIF) COATS-Haenszel USING DIFFERENT AREAS UNDER THE TOWN AND VILLAGE IN NATIONAL TEST DEVICE IN BANTEN IPA SD ( Primary School) - Sukemi (lppm Universitas Negeri Jakarta, 2017)
Analysis of Differential Item Function (DIF) / otherness Function Item is an analysis conducted on a set of tests to determine the bias point. Bias grains occur because of differences in background of respondents test, while a good test devices have qualities of objectivity, transparency, accountability and non-discriminatory. This study aimed to describe the test items were contracted Differential Item Function (DIF) at the National Examination IPA SD devices based on differences in urban and rural areas in the province of Banten using Mantel-Haenszel statistical methods. Mantel Haenszel method is a statistical method that belong to the classical theory to estimate the capability (ability) answered correctly and one of the two groups Referring (City group) and Focus (village groups). In the analysis of the National Examination tests conducted by IPA SD urban and rural areas because basically learning science provide insights into the learners to study the nature of life in a real and every region has a characteristic difference in the character of each. Learners tendency of characters to characters who occupied a very large area of influence, so that the DIF analysis was performed on the test device by city and village. The method used in this research is descriptive quantitative method based on the translation of factual data and systematically based on numerical analysis using statistics, with a population of primary school learners based on the classification of the city of Dan Village. Selection of the sample was done by using stratified random sampling by classifying and analyzing each unit of analysis. Data is collected using secondary data from relevant agencies and government agencies manually and online. The analysis carried out quantitative analysis using the Mantel-Haenszel method. The results of the analysis indicate that there Differential Item Function (DIF) on items of National Examination test devices based on the analysis of urban and rural differences. DIF infected grain on the test device, twelve grains of forty grains, with a tendency to point to areas of the city of five items and the tendency to rural areas totaled seven points. Data is collected using secondary data from relevant agencies and government agencies manually and online. The analysis carried out quantitative analysis using the Mantel-Haenszel method. The results of the analysis indicate that there Differential Item Function (DIF) on items of National Examination test devices based on the analysis of urban and rural differences. DIF infected grain on the test device, twelve grains of forty grains, with a tendency to point to areas of the city of five items and the tendency to rural areas totaled seven points. Data is collected using secondary data from relevant agencies and government agencies manually and online. The analysis carried out quantitative analysis using the Mantel-Haenszel method. The results of the analysis indicate that there Differential Item Function (DIF) on items of National Examination test devices based on the analysis of urban and rural differences. DIF infected grain on the test device, twelve grains of forty grains, with a tendency to point to areas of the city of five items and the tendency to rural areas totaled seven points. The results of the analysis indicate that there Differential Item Function (DIF) on items of National Examination test devices based on the analysis of urban and rural differences. DIF infected grain on the test device, twelve grains of forty grains, with a tendency to point to areas of the city of five items and the tendency to rural areas totaled seven points. The results of the analysis indicate that there Differential Item Function (DIF) on items of National Examination test devices based on the analysis of urban and rural differences. DIF infected grain on the test device, twelve grains of forty grains, with a tendency to point to areas of the city of five items and the tendency to rural areas totaled seven points.